A framework for analyzing and practicing Integrative Governance: The case of global animal and conservation governance. (December 2018) - Visseren-Hamakers, Ingrid J
This article presents a framework to analyze and practice Integrative Governance, defined as the theories and practices that focus on the relationships between governance instruments and/or systems. The need to pay explicit attention to such relationships is increasingly recognized, especially in achieving the transformative change needed for sustainable development. The Integrative Governance framework focuses on explanatory analyses of the relationships and performance of governance instruments and/or systems, and is inspired by a pragmatic theoretical perspective. It includes three steps of analysis, with the first focused on the governance instruments and the relationships between them, the second on the combined performance of governance systems, and the third on explanations for the relationships and performance. Especially for this third step, insights from different theoretical perspectives are used, incorporating insights from rational choice theory, institutionalism, constructivism and critical theory. The application of the framework is illustrated by the example of the global animal and conservation governance systems. The preliminary analysis shows that the global conservation governance system is relatively more developed than the global animal governance system. The latter is mainly focused on animal health, with fewer instruments on welfare, and none on animal rights. The former includes more governance instruments and has some systems in place for monitoring implementation. The performance of both systems however remains limited, and there are few interactions between the systems. Main explanations include the interests of countries involved in the governance systems, the dominant anthropocentric discourses, and the current mostly animal-unfriendly and unsustainable political economy. Applying the Integrative Governance framework enables an enhanced understanding of the multiple and intertwined explanations of the relationships and performance of governance systems, allowing academics and practitioners to develop more realistic, durable solutions both in the shorter and longer term.